Big data analytics capability and supply chain performance: The mediating roles of supply chain resilience and innovation - Mohammad Bahrami; Sajjad Shokouhyar; Atiyeh Seifian (Modern Supply Chain Research and Applications, 2022)
Purpose - Big data analytics (BDA) capabilities can affect supply chain performance in several ways. The main purpose of this study was to understand how BDA capabilities could affect supply chain performance through supply chain resilience and supply chain innovation. Design/methodology/approach - The study adopted a cross-sectional approach to collect survey-based responses to examine the hypotheses. Accordingly, 187 responses were collected and analyzed using partial least squares (PLS) in the SmartPLS3. Findings - The results showed that BDA capabilities improve supply chain performance through resilience and innovation of the supply chain. Originality/value - The present study also contributed to the existing literature by demonstrating the mediating role of supply chain resilience and supply chain innovation between BDA capabilities and supply chain performance. In this context, some theoretical and managerial implications were proposed and discussed.
Keywords: 650; Big data analytics capabilities; Dynamic capability view; Innovation; Resilience; Supply chain performance